Towards a Test Case Generation Tool Based on Functional Requirements - Fernandes, Daniel David; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2020)
Software Testing is a process which aims to find defects during a software lifecycle. It involves time-consuming activities and may be impossible to guarantee the software's perfect functioning due to the numerous cases that must be processed accurately. The software must ensure compliance with functional requirements, but most current test case generation tools lack functionalities based on functional requirements. Therefore, they often point to defects that may not match software requirement specifications or report cases considered defects according to these specifications. In this scenario, to support functional requirements testing processes by generating requirement-based tests, we propose the AutomTest tool. It uses equivalence class division and boundary value analysis approaches aiming to increase defect detection efficiency. To evaluate AutomTest, we applied a two-step exploratory study. Initially, we used AutomTest to correct exercises solved by computer science students, and then students with programming experience used our tool to find defects in three predefined scenarios. AutomTest's performance presented satisfactory results in accuracy, code coverage, mutation analysis, and efficiency in finding defects.